Efektivitas Penggunaan Media Gambar Dalam Layanan Informasi Meningkatkan Interaksi Sosial Siswa SMPN 34 Pekanbaru - Ade Afrila; Raja Rahima; Rani Navila Sari (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2021)
This research aimed at knowing the effectiveness of using Picture media on information service to increase student social interaction.  The problems at State Junior High School 34 Pekanbaru were the students who had low social interaction, whodaydreamed, who were closed, unconfident, and alone.  Quantitative approach was used in this research by using pre-Experimental research with the on group Pretest-Posttest design. The object of this research was the effectiveness of using Picture media on information service to increase student social interaction. The subjects of this research were students having low social interaction and they were 40 students. Random Sampling technique was used in this research.The techniques of collecting the data were questionnaire, observation, and documentation. The instruments of this research were valid with 0.361 Correlation Coefficient and 0.978the reliability.  The technique of analyzing the data was Wilcoxon’s Signed Ranks Test.  The research findings showed that student social interaction before being given Picture media in information service was on low category and the mean score was 64.65.  After being given Picture media in information service, student social interaction increased to the high score and the mean score was 119.9.  The test result of Ha showedthe significant score 0.05, 0.000 was lower than 0.05, so Ha was accepted, and the contribution of X to Y was 78.3%.